Design And Fabrication Of Small Scale Extrusion Machine - Jamaludin, Mohd Nazim (Universiti Sains Malaysia, 2003)
This thesis is a project of design and fabrication of Small Scale Extrusion Machine. In development the machine, the principle of extrusion process need to study and understand to determine the components of the machine. Extrusion process is another method to form and shape metals and plastics beside the other process such as injection molding, blow molding and rotational molding. The machine is designed to extrude raw materials such as plasticine and powder in certain shape where screw will rotate to force the raw material from feed hopper to shape-forming die. Design process start after know the functional of the components and the conceptual design of the machine. During design phase, the shapes and dimensions components will follow the guideline given by conceptual design. After designing completed, the suitable materials is selected to fabricate the components. Many machines are used to fabricate the components that drill, lathe, milling and rapid prototyping machine. The machines used depend on the components to fabricate and the materials used. All components are assembled after fabrication completed to run extrusion machine by using motor. First run will evaluate the extrusion machine performance. Improvement and modification need to be done to the design if components are not functioning properly and effectively. Extrusion machine will run again until the performance is satisfied.